Microplastics and child health: a scoping review of prenatal and early-life exposure routes and potential health risks - Nadarasan, Sakuntala; Phuna, Zhi Xin; Zaman, Rahela; Tan, Chung Keat; Bustami, Normina Ahmad; Bin Ho, Yu; Kosasih, Stephanie Julia; Tan, Eugenie Sin Sing (Elsevier, 2025)
Microplastics (MPs) is defined as plastic particles less than 5 mm. MPs have become a major environmental pollutant and it is originating from the breakdown of larger plastic waste. This article aims to explore MPs exposure to human health, particularly its potential effects during early developmental years. Studies reveal that MPs exposure begins via intra-uterine route, where MPs were detected in the placenta, amniotic fluid, umbilical cord, fetal membranes, and umbilical vein blood. As infants developed, the MPs exposure continued via breast milk, milk storage bags, formula, feeding bottles, and even from pacifiers. During early childhood, exposure routes can be from 3 different routes, including dermal contact (clothing, childcare products), ingestion (bottled milk, school dust, playground sand, sugar, salt), and inhalation (toy blocks, play mats, indoor air). The review also highlights the potential health risks to vital organs and systems from prenatal as well as postnatal MPs exposure in in vivo studies. These includes the optical, neurological, cardiovascular, pulmonary, hepatic, urinary, digestive, skeletal, lymphatic and reproductive systems. Given their small size and potential toxicity, MPs may disrupt these important developmental processes, leading to long-term health consequences. This article explores the route of MPs exposure with the potential severity and health impacts of those exposure, especially for fetuses, infants, and children. By doing so, it aims to identify any missing knowledge in this area. This research will serve as a foundation for designing future studies that identify health risks in generations exposed to MPs from a very young age.